2018
DOI: 10.3390/molecules23113004
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative, Proapoptotic, Antioxidant and Antimicrobial Effects of Sinapis nigra L. and Sinapis alba L. Extracts

Abstract: High Brassicaceae consumption reduces the risk of developing several cancer types, probably due to high levels of glucosinolates. Extracts from Sinapis nigra L. (S. nigra) and Sinapis alba L. (S. alba) have been obtained from leaves and seeds under different conditions using ethanol/water mixtures because their glucosinolates are well accepted by the food industry. The EtOH/H2O 8:2 mixture gives better yields in glucosinolate amounts from ground seeds, mainly, sinalbin in S. alba and sinigrin in S. nigra. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Seed extracts that portrayed such benefits as chemopreventive, cytotoxic and antimicrobial include: - seed extracts of Brassica juncea L. containing 3- butenyl ITCs [ 35 ], Lobularia libyca [ 36 ], Carica papaya L. rich in benzyl GS [ 37 ], mustard seed powder [ 38 ], Sinapsis alba L. and Sinapsis nigra L. with high content of sinalbin and sinigrin, respectively [ 39 ]. GMG isolated from Moringa oleifera L. seeds possessed chemopreventive [ 40 , 41 , 42 ], insect larvae deterrence [ 43 ], antibacterial [ 44 ] and anti-inflammatory activity [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seed extracts that portrayed such benefits as chemopreventive, cytotoxic and antimicrobial include: - seed extracts of Brassica juncea L. containing 3- butenyl ITCs [ 35 ], Lobularia libyca [ 36 ], Carica papaya L. rich in benzyl GS [ 37 ], mustard seed powder [ 38 ], Sinapsis alba L. and Sinapsis nigra L. with high content of sinalbin and sinigrin, respectively [ 39 ]. GMG isolated from Moringa oleifera L. seeds possessed chemopreventive [ 40 , 41 , 42 ], insect larvae deterrence [ 43 ], antibacterial [ 44 ] and anti-inflammatory activity [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial activity of plant extracts possessing therapeutic potential relies on the presence of volatiles, among which GSs and GSHP compounds have been well identified. Studies focusing on these compounds and their antimicrobial activities show that active compounds affect pathogens’ membrane integrity [ 127 ], intracellular potassium release [ 10 ], inhibit growth in pathogens [ 22 , 36 , 39 , 51 , 52 , 53 , 54 , 79 , 80 , 83 , 87 , 89 , 90 ], kill pathogens [ 81 , 82 , 88 ] and change physiochemical surface properties and charges. Inhibitory effects of GSs and GSHPs can be non-selective [ 59 ] or may vary between different pathogens, as illustrated by allyl and phenylpentyl ITCs in A. rusticana which has higher antifungal activity than antibacterial activity [ 80 ].…”
Section: Benefits Of Natural and Synthetic Gss And Gshpmentioning
confidence: 99%
See 1 more Smart Citation
“…From the cruciferous group, mustard (Sinapis alba) seeds are interesting sources of polyphenols. Mustard seeds are largely used as a condiment in food preparations [58]. A recent study indicated that the phenolic profile of mustard seeds hulls comprises sinapic acid and its derivatives sinapine and sinapoyl glucose [52].…”
Section: Lentil (Lens Culinaris)mentioning
confidence: 99%
“…Recently, we became interested in sinapine (1 as its thiocyanate, Scheme 1) [36][37] , an alkaloid which can be found in white mustard (Sinapis alba) [38][39] and canola (Brassica sp.) [40][41] because some interesting biological activities have been reported for this hybrid composed from (E) 4-hydroxy-3,5dimethoxycinnamic acid and choline.…”
Section: Introductionmentioning
confidence: 99%